Anti-Inflammatory, Analgesic Evaluation and Molecular Docking Studies of N-Phenyl Anthranilic Acid-Based 1, 3, 4-Oxadiazole Analogues. (25th September 2013) - Bala, Suman; Kamboj, Sunil; Saini, Vipin; Prasad, D. N.
Abstract : A novel series of N-phenyl anthranilic acid-based 1, 3, 4-oxadiazoles were prepared (4a–h ) and subjected to anti-inflammatory, analgesic activity and molecular docking studies to target cyclooxygenase-2 enzyme. 1, 3, 4-Oxadiazole derivatives were screened for anti-inflammatory activity in carrageenan-induced rat paw edema and analgesic activity by tail immersion method. In synthesized compounds, the free carboxylic group, which is responsible for gastric side effects, was derivatized by heterocyclic 1, 3, 4-oxadiazole bioactive core, which showed good interaction with COX-2 receptor with good docking score. Among all the synthesized compounds, 4e and 4f have emerged out as potential COX-2 inhibitors.